2015
DOI: 10.1589/jpts.27.3381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nintendo Wii Fit Plus training on ankle strength with functional ankle instability

Abstract: [Purpose] The objective of this study was to examine the effects of a training program using the Nintendo Wii Fit Plus on the ankle muscle strengths of subjects with functional ankle instability. [Subjects and Methods] This study was conducted using subjects in their 20s who had functional ankle instability. They were randomized to a strengthening training group and a balance training group with 10 subjects in each, and they performed an exercise using Nintendo Wii Fit Plus for 20 minutes. In addition, every p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…Comparison of mean values of stability index between conventional therapy and VR training showed significant improvement of all stability index OASI, APSI, and MLSI in favor of VR, similar to previous findings revealing significant improvement of static and dynamic balance in subjects with functional ankle instability (16).…”
Section: P R E P R I N Tsupporting
confidence: 88%
See 1 more Smart Citation
“…Comparison of mean values of stability index between conventional therapy and VR training showed significant improvement of all stability index OASI, APSI, and MLSI in favor of VR, similar to previous findings revealing significant improvement of static and dynamic balance in subjects with functional ankle instability (16).…”
Section: P R E P R I N Tsupporting
confidence: 88%
“…The program included: lunge, single leg extension, sideways leg lift, single leg twist, and rowing squat as strength exercises. Soccer heading, tight rope walks, ski slalom, table tilt, and snowboard slalom as balance exercises (16).…”
Section: Interventionmentioning
confidence: 99%
“…Virtual reality training was introduced as an auxiliary rehabilitation tool for completing the treatment for subjects with lower limb injuries. 1317 These games, not only leaded to excitement and entertainment but had been also expressed to improve balance and power. 16 Conventional exercises were not attractive and motivating for subjects, in turn, this was a disadvantage for them.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Alfieri et al [12] suggest that multisensory exercise programs can improve both postural control and muscle strength of invertors and evertors. Other studies showed that postural control training strengthens the invertors and evertors [13], and that strength training besides improved muscle strength of all ankle muscle groups results in improved postural control [14]. In addition, greater use of ankle evertors owing to their improved strength could be associated with a reduction in mediolateral sway during sufficiently demanding postural tasks [15].…”
Section: Introductionmentioning
confidence: 99%